Strategi Mengelola Perubahan dalam Meningkatkan Kualitas Pendidikan di Lembaga Pendidikan Islam: Strategies for Managing Change in Improving Quality Education in Islamic Educational Institutions - Dima Noor Ziehad; Adi Rosadi; Ahmad Yani (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2026)
This study addresses the persistent challenges of improving education quality in Islamic educational institutions, where systematic approaches to managing change remain underexplored. It aims to identify change management strategies, analyze key challenges, explore collaborative and training approaches, and formulate an adaptive change management model for Islamic educational institutions. Using a qualitative systematic literature review following PRISMA guidelines, ten relevant articles from Scopus, Web of Science, PubMed, and Google Scholar (2015–2025) were analyzed. The findings reveal that effective strategies include transformational leadership, adaptive curricula, technology integration, and SWOT analysis, supported by collaborative communication, stakeholder involvement, and continuous human resource development. Major challenges are resistance to change, limited human resources, inadequate infrastructure, and poor coordination. The study concludes that successful change management in Islamic education depends on integrating Islamic values (syura, amanah, muhasabah) with modern management frameworks such as Lewin’s model, ADKAR, and POAC. The implications highlight the need for holistic, value-based change models to enhance institutional quality and sustainability.